Incarnating Authority: A Critical Account of Authority in the Church - Avis, Paul; Berlis, Angela; Knoepffler, Nikolaus; O’Malley, Martin (utzverlag GmbH, 2019)
The articles of this collection examine contemporary structures of authority in the Christian church. Scholars critically explore their own churches, looking at historical as well as contemporary discussions about authority: the conciliar tradition, secular developments, experiences of non-ordained ecclesial leadership, on to more confessional principles, rules, and practices relevant for church governance. Contributions represent the following traditions: Anglican, Old Catholic, Roman Catholic, Orthodox, Lutheran, Methodist, and Reformed. The goal is not only to theorize about authority abstractly, but also to explore potential paths for closer ecclesial union and ecumenical action.   Biographische Informationen Authors: Paul Avis, Angela Berlis, David Chapman, Irina Deretić, Jan Hallebeek, Nikolaus Knoepffler, Martin Leiner, Martin O’Malley, Martyn Percy, Andrew Pierce, Catherine Shelley, Jeremy Worthen Reihe ta ethika - Band 18